2022
DOI: 10.21831/inersia.v18i1.48260
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sifat Mekanik Lentur Papan Laminasi Kombinasi Bambu Petung dan Bambu Ater

Abstract: Kemajuan teknologi memunculkan alternatif bahan bangunan pengganti kayu, seperti bambu laminasi. Laminasi bambu menggunakan kombinasi dua jenis bambu yaitu bambu petung dan bambu ater. Bambu petung memiliki kuat lentur lebih besar dibandingkan bambu ater dapat meningkatkan nilai MOR dan MOE. Penelitian ini bertujuan untuk mengetahui kuat lentur, pengaruh susunan lapisan laminasi, pengaruh penambahan bambu petung pada laminasi bambu ater dari laminasi kombinasi dua jenis bambu. Pengujian kuat lentur papan lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
1
1
Order By: Relevance
“…However, compared to the study by Sulistianingsih et al [29], the moisture content value of nine bamboo has an average value of 12.9%. Belatrix et al [28] reported Ater bamboo laminated boards have an average moisture content value of 12.58%, where both values are higher than the moisture content values in this study.…”
Section: Moisture Contentcontrasting
confidence: 70%
See 1 more Smart Citation
“…However, compared to the study by Sulistianingsih et al [29], the moisture content value of nine bamboo has an average value of 12.9%. Belatrix et al [28] reported Ater bamboo laminated boards have an average moisture content value of 12.58%, where both values are higher than the moisture content values in this study.…”
Section: Moisture Contentcontrasting
confidence: 70%
“…Sulistianingsih et al [27] reported that the moisture content value of Andong bamboo laminated boards has an average value of 11.1%. Belatrix et al [28] reported that the moisture content of laminated boards made from a combination of Betung and Ater bamboo had an average value of 12.12%. In addition, Iswanto et al [11] regarding the manufacture of belangke bamboo-based particleboard, which also has a lower moisture content value ranging from 6.56% -7.96%.…”
Section: Moisture Contentmentioning
confidence: 99%
“…Penyebab terjadinya Perubahan dimensi dipengaruhi oleh hilangnya air terikat dari dinding sel yang menyebabkan sel mengalami pengerutan dan terjadilah penyusutan (Mochsin et.al, 2014). (Belatrix, 2022a).…”
Section: Penyusutan Tebalunclassified
“…Ater bamboo (Gigantochloa atter Kurz.) or what is often called ater bamboo has bright green to dark green stems and a diameter of about 5 -10 cm, a segment length of about 40 -50 cm with a stem height of up to 22 m (Belatrix, et al, 2022). -Malvaceae family with hibiscus or new plant species (Hibiscus tiliaceus L.) where the tree trunks are used as rope, considering that hibiscus trees function as reinforcement in composites because hibiscus skin fiber has a continuous fiber structure and a strong natural weave (Nurudin, 2011), and, hibiscus wood fiber is known to contain low lignin (Aulya, et al, 2020).…”
Section: Figure 12 Procession Ampa Fare Aspect Botany and Conservatio...mentioning
confidence: 99%